2021
DOI: 10.21182/jmisst.2020.00192
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve of Minimally Invasive C1-C2 Trans-articular Screw Fixation (MIS-TAS): Over A Period of Five Years

Abstract: Objective: To evaluate the learning curve associated with minimally invasive surgery (MIS) in posterior C1-C2 trans-articular (TAS) screw fixation based on surgical and clinical parameters. Also, to report the challenges faced and measures to overcome them. Methods: 84 patients who underwent C1-C2 MIS-TAS between 2009-2014 were included in the study and were divided into four quartiles (q) (21 patients each) based on the date of their surgery with each consecutive group serving as a control for prior. Pre-and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Raut al et al [18] reported their 5-year experience with C1-C2 minimally invasive transarticular fixation, which showed a progressive reduction in operative time and blood loss over the evaluated period by exposing perioperative parameters in quartiles. The learning curve of our surgical technique has also demonstrated a tendency to reduce operative time, blood loss, and hospitalization over the last decade (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Raut al et al [18] reported their 5-year experience with C1-C2 minimally invasive transarticular fixation, which showed a progressive reduction in operative time and blood loss over the evaluated period by exposing perioperative parameters in quartiles. The learning curve of our surgical technique has also demonstrated a tendency to reduce operative time, blood loss, and hospitalization over the last decade (Figure 6).…”
Section: Discussionmentioning
confidence: 99%